Double Track System for Child Convictions for Sexual Violence In North Sumatera: Perspective of Restorative Justice - Purba, Nelvitia; Suriani, Suriani; Ismail, Ismail; Ismail, Wan Nor Azilawanie Tun; Saragih, Al-Kausar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Such rapid advances in technology are the cause of criminal acts of sexual violence committed by children. So far, sanctions against perpetrators of criminal acts of violence against children have been carried out by children under 12 years of age by returning them to their parents, guardians and adoptive parents. This research was conducted with the aim of knowing the forms of criminal acts of sexual violence and their handling, sanctions and criminal action (Double Track System) for the Development and Education of Criminal Sexual Violence (COSV) against Children in North Sumatra. This research uses empirical legal methods analyzed with the theory of restorative justice. Data was collected by means of in-depth interviews and documentation. The informants interviewed were academics, legal activists and community leaders. Documents refer to relevant journal articles, books and references. The results of the research show that the application of punishment to minors, especially children under 12 years of age who commit criminal acts of sexual violence, receives very serious attention considering that sexual violence has a psychological impact on the victims. Criminal sanctions and providing action in the form of guidance and education for perpetrators of sexual violence, implementing regulations are very necessary as guidelines for judges in handing down decisions as regulated in Law Number 11 of 2012. According to the theory of restorative justice, children who commit sexual violence must be resolved in a dignified manner with guidance and education, so that children's rights are not neglected.